The impact of corporate social responsibility on the use of earnings management in the context of internal financial and macroeconomic factors: The case of Lithuania - Diana Bachtijeva; Daiva Tamulevičienė; Rasa Subačienė (Economies, 2024)
Earnings management is a widespread phenomenon in practice, with researchers therefore focusing on trying to understand what motives and factors lead to companies engaging in earnings management. In addition to internal financial and macroeconomic factors, the influence of institutional factors including corporate social responsibility (CSR) has been widely studied in recent years. In Lithuania, there have been no studies on the manipulation of accounting information in socially responsible companies. Therefore, this study aims to identify the impact of CSR on the application of earnings management in the context of internal financial and macroeconomic factors. The results of this study are significant as they not only enable assessing the impact of social responsibility on the application of earnings management in Lithuanian companies, but also the influence of macroeconomic factors such as the gross domestic product (GDP), inflation, foreign direct investment (FDI), average wages, and unemployment, as well as internal financial factors such as leverage, returns on assets (RoA), and the profitability of EBIT. The results show that CSR reduces the use of earnings management, regardless of whether it is accrual-based or real earnings management. Additionally, this analysis demonstrates that, among the internal financial factors, leverage carries the most substantial influence. The higher a company's leverage, the more inclined that company is to use earnings management. Exploring the impact of macroeconomic indicators, it was found that the GDP, inflation, and unemployment rate have a statistically significant impact on the use of earnings management, albeit only if the firm uses accrual-based earnings management and adopts a profit-enhancing strategy.
Keywords: 330; accrual-based earnings management; real earnings management; corporate social responsibility; Lithuanian companies